2012
DOI: 10.3144/expresspolymlett.2012.103
|View full text |Cite
|
Sign up to set email alerts
|

Epoxy/PCL nanocomposites: Effect of layered silicate on structure and behavior

Abstract: Abstract. The effect of clay-induced morphological transitions on the structure formed in the course of reactively induced phase separation (RIPS) and its impact on the properties of epoxy/polycaprolactone (PCL) nanocomposites were studied. The effect of organophilized montmorillonite on the behavior of epoxy containing 5-30% PCL was strongly dependent on the epoxy/PCL system composition. With a supercritical 20% PCL content, the increasing amounts of clay led to changes in the morphology that produced phase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
30
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 45 publications
7
30
0
1
Order By: Relevance
“…The single but broad Tg peak indicates good compatibility between the EP(H) and PCL. Its shift toward lower temperature can be assigned to a reduction in the apparent crosslink density or increase in the free volume (9). Similar results were reported by other EP/PCL systems, too (9,14).…”
Section: Dmasupporting
confidence: 76%
See 2 more Smart Citations
“…The single but broad Tg peak indicates good compatibility between the EP(H) and PCL. Its shift toward lower temperature can be assigned to a reduction in the apparent crosslink density or increase in the free volume (9). Similar results were reported by other EP/PCL systems, too (9,14).…”
Section: Dmasupporting
confidence: 76%
“…Its shift toward lower temperature can be assigned to a reduction in the apparent crosslink density or increase in the free volume (9). Similar results were reported by other EP/PCL systems, too (9,14). The presence of PCL becomes, however, clearly detectable only for EP(H)/PCL-50 where and additional peak at T45 o C appears.…”
Section: Dmasupporting
confidence: 76%
See 1 more Smart Citation
“…In some cases, suitable modifications can enhance HNT efficiency [17,18]. However, the evaluation of the structure-directing potential of HNT in polymer [19][20][21][22][23] is in its infancy stage, especially in comparison with that of oMMT [24][25][26][27]. Although the application of PLA and other high performance polyesters in the form of short reinforcing fibres [28,29] in polymer-polymer composites could be a radical alternative to the use PCL/ PLA blends, a significant limitation of this method is the difficult dispersion of compliant fibres in the polymer matrix and their relatively poor adhesion to it [30].…”
Section: Introductionmentioning
confidence: 99%
“…The minority phase, namely the thermoplastic-rich phase, is continuous due to its strengthened viscoelasticity during phase separation. In our recent work [28,29] we showed that nanoclay can significantly affect the behaviour of epoxy/ PCL systems containing 5-30% PCL. The radical morphological transformations consisting of phase inversion for 20% PCL content due to increasing clay content led to a substantial improvement of the mechanical behaviour.…”
Section: Introductionmentioning
confidence: 99%